Immunohistochemical features of multifocal melanoacanthoma in the hard palate: A case report - Das Chagas E Silva de Carvalho, Luis Felipe [UNESP]; Farina, Vitor Hugo [UNESP]; Cabral, Luiz Antonio Guimarães [UNESP]; Brandão, Adriana Aigotti Haberbeck [UNESP]; Coletta, Ricardo Della; Almeida, Janete Dias [UNESP] (Springer Nature, 2013)
Background: Melanoacanthoma (MA) has been described in the oral mucosa as a solitary lesion or, occasionally, as multiple lesions. MA mainly affects dark skinned patients and grows rapidly, showing a plane or slightly raised appearance and a brown to black color. The differential diagnosis includes oral nevi, amalgam tattoos, and melanomas. We report here the case of a 58-year-old black woman who presented multiple pigmented lesions on the hard palate. Case presentation. Based on the differential diagnosis of melanoma, a punch biopsy (4 mm in diameter) was performed. The material was fixed in 10% formalin, embedded in paraffin, and stained with hematoxylin-eosin or submitted to immunohistochemical analysis. Immunohistochemistry using antibodies against protein S-100, melan-A, HMB-45, MCM-2, MCM-5, Ki-67 and geminin was performed. Immunohistochemical analysis revealed strong cytoplasmic immunoreactivity of dendritic melanocytes for proteinS-100, HMB-45 and melan-A.Positive staining for proliferative markers (MCM-2, MCM-5, Ki-67) was only observed in basal and suprabasal epithelial cells, confirming the reactive etiology of the lesion. The diagnosis was oral Melanoacanthoma (MA). Conclusion: The patient has been followed up for 30 months and shows no clinical alterations. MA should be included in the differential diagnosis of pigmented lesions of the oral cavity. © 2013 das Chagas e Silva de Carvalho et al.; licensee BioMed Central Ltd.
Keywords: Melanoacanthoma; Mouth; Pigmented lesions; acanthoma; case report; female; hard palate; human; immunohistochemistry; metabolism; middle aged; mouth tumor; pathology; Acanthoma; Female; Humans; Immunohistochemistry; Middle Aged; Mouth Neoplasms; Palate, Hard